Study of Female Rider Visual Perception Toward Scooter Designs in Indonesia - Linda Lukita; Achmad Syarief; Slamet Riyadi; Andar Bagus Sriwarno (ITB Journal Publisher, LPPM ITB, 2020)
This study consisted of a perception evaluation and identification of scooter shapes that are attractive to female riders. A survey using a Likert scale was conducted on 150 female scooter riders, providing an evaluation of six different scooter shapes representing scooter designs in Indonesia. The result of the descriptive analysis showed that scooter designs in Indonesia are perceived as high-quality, comfortable to ride, able to be used by family members, fun to ride, relaxing, and giving self-confidence when they are ridden, all of which are physio-, socio- and psycho-pleasure factors, thus only achieving the visceral and behavioral phases. These perceptions are in accordance with the female gender (communal, high emotion and empathy). The scooter models considered to be attractive to female riders had perceptions related to the ideo-pleasure factor determined by shape details in the scooter design. The results of factor analysis showed a different composition of perception factors among scooter models. The conclusion of this study is that in addition to size, type and shape characteristics, designs, both the overall design and design details as well as gender characteristics influence the difference in visual perception by female riders toward scooter designs.